PERAN SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN REKLAME PILPRES 2024 - Trianto, Agus; Yonnawati, Yonnawati; Rahmaini, Putri (DEMOKRASI, 2025)
ABSTRACT Abstract: The 2024 Presidential Election in Indonesia led to a surge in campaign billboard installations, which often violated spatial planning regulations and public order. This study analyzes the role of the Civil Service Police Unit (Satpol PP) in managing the regulation of campaign billboards during the 2024 Presidential Election in Tulang Bawang Regency. A qualitative approach was employed through observations, in-depth interviews, and documentation, with data analyzed using the interactive model of Miles and Huberman. Key informants included Satpol PP officials and local community members.The findings indicate that Satpol PP plays a crucial role in enforcing regional regulations, maintaining city aesthetics, and ensuring social order during the campaign period. However, challenges such as resistance from billboard installers, limited resources, operational facilities, and political pressure often hinder their performance. Dialogical and persuasive strategies are employed to mitigate conflicts and enhance public awareness regarding billboard regulations. Collaboration between Satpol PP and other agencies, such as the Department of Transportation and the Department of Public Works, is considered essential for effective enforcement. Furthermore, improving human resources and utilizing technology, such as digital applications to monitor and record illegal billboards, are recommended to enhance efficiency. Overall, Satpol PP holds a pivotal role in ensuring order and fairness during the campaign period. Support from local governments, communities, and related agencies is critical to the success of their efforts. This study provides practical recommendations for improving billboard management during national political events. Keyword: Billboards, Regulatio, Satpol PP ABSTRAK Abstrak: Pemilihan Presiden 2024 di Indonesia menyebabkan lonjakan pemasangan reklame kampanye, yang sering melanggar aturan tata ruang dan ketertiban umum. Penelitian ini menganalisis peran Satuan Polisi Pamong Praja (Satpol PP) dalam penertiban reklame Pilpres 2024 di Kab. Tulang Bawang. Pendekatan kualitatif digunakan melalui observasi, wawancara mendalam, dan dokumentasi, dengan analisis data berdasarkan model interaktif Miles dan Huberman. Informan utama adalah pejabat Satpol PP dan masyarakat setempat. Hasil penelitian menunjukkan bahwa Satpol PP berperan penting dalam menegakkan peraturan daerah, menjaga estetika kota, dan menciptakan keteraturan sosial selama kampanye. Namun, tantangan seperti resistensi dari pemasang reklame, keterbatasan sumber daya, fasilitas operasional, serta tekanan politik sering menghambat kinerja mereka. Strategi dialogis dan persuasif digunakan untuk mengurangi konflik serta meningkatkan kesadaran masyarakat terhadap aturan reklame. Kolaborasi Satpol PP dengan instansi lain, seperti Dinas Perhubungan dan Dinas Pekerjaan Umum, dianggap penting untuk efektivitas penertiban. Selain itu, disarankan peningkatan SDM dan pemanfaatan teknologi, seperti aplikasi digital, untuk memantau dan mendata reklame ilegal secara lebih efisien. Secara keseluruhan, Satpol PP memegang peranan penting dalam memastikan keteraturan dan keadilan selama masa kampanye. Dukungan pemerintah daerah, masyarakat, dan instansi terkait sangat diperlukan untuk keberhasilan tugas ini. Penelitian ini memberikan masukan praktis untuk meningkatkan pengelolaan reklame dalam momen politik nasional. Kata Kunci : Reklame, Penertiban, Satpol PP